Hirarc: a tool of safety imporvement in the construction industry - Bakri, Ahmadon; Mohamad Zin, Rosli; Omar, Wahid; Lee, Chia Kuang (2008)

(untitled)
The construction industry plays a vital role in Malaysia’s economy. However, construction industry has been labeled as extremely dangerous and highly risky. In Malaysia, the number of accidents occurred on construction sites is considered high in comparison to other industries. This paper reports on the study carried out to identify the effectiveness of the implementation of HIRARC in reducing accidents on construction sites, based on 10 different projects that implemented HIRARC. From structured interviews conducted to 10 safety personnel who implemented HIRARC in their projects, it has been found that the basic process of HIRARC was 100 % implemented and carried out. The study also revealed that each and all process of HIRARC was found to be “effective”. In addition to that, another structured interviews conducted to 26 consultants engaged with construction projects on the effectiveness of the implementation of HIRARC shows that HIRARC is also “effective” in identifying all potential hazards; assessing all the risks of hazards; making adequate risk control and accident preventive measures; acting as an occupational safety and health management system; and reducing accidents on construction sites. Finally, a comparison is made on the safety performance between construction projects which implemented HIRARC and construction projects which did not implement HIRARC. The findings show that construction project with HIRARC is actually more effective in reducing accidents on construction sites. In conclusion, the implementation of HIRARC is indeed effective in reducing accidents on construction sites.